Earnings inequality in the Brazilian formal sector: The role of firms, education, and top incomes 1994-2015 - Marcelo Cortes Neri; Cecilia Machado; Valdemar Rodrigues de Pinho Neto (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper documents the evolution and the determinants of earnings inequality in the Brazilian formal sector from 1994 to 2015, using establishment level data. In 2015, schooling explained 33 per cent of overall inequality. Firm-specific effects explain 65 per cent of total inequality level and 76 per cent of the inequality fall observed. The downward inequality trend parallels the one seen in household surveys. However, the distributive decompression goes only until the 90th percentile, which is in line with Personal Income Tax based evidence. The share of inequality explained by top 1 per cent and 0.1 per cent incomes rose 43 per cent and 91 per cent, respectively.
Keywords: J31; I24; 330; earnings inequality; linked employer-employee data; firm and worker heterogeneity; Brazilian inequality; entropy indexes; firms fixed effects